2022
DOI: 10.59331/jasd.v5i4.363
|View full text |Cite
|
Sign up to set email alerts
|

Economics of Yam Production and Marketing in Taraba State, Nigeria

Abstract: The study analysed the economics of yam production and marketing in Taraba State. Specifically, the study described the socio-economic characteristics of yam producers and marketers, determined cost and returns of producers and marketers. A multi-stage purposive and simple random sampling was employed in the study. Data were collected with the aid of structured questionnaire. Descriptive statistics, net farm income and regression analysis were used in analysing the data. The result of the analysis showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…In the case of this study, the index was higher in both seasons, indicating good economic prospects for the cultivation of yams. In a study conducted by Akintunde et al [49] in Nigeria, the authors indicated that the production and marketing of yams are highly profitable, thus supporting the findings of this work. According to Udemezue and Nnabuife [50], among the challenges of yam producers that can affect the economy are inadequate extension services, pest and disease attacks, adverse weather conditions, high labor costs, high cost of yams, and the use of unimproved seeds.…”
Section: Profitability Indexsupporting
confidence: 84%
“…In the case of this study, the index was higher in both seasons, indicating good economic prospects for the cultivation of yams. In a study conducted by Akintunde et al [49] in Nigeria, the authors indicated that the production and marketing of yams are highly profitable, thus supporting the findings of this work. According to Udemezue and Nnabuife [50], among the challenges of yam producers that can affect the economy are inadequate extension services, pest and disease attacks, adverse weather conditions, high labor costs, high cost of yams, and the use of unimproved seeds.…”
Section: Profitability Indexsupporting
confidence: 84%